2018
DOI: 10.1182/blood-2018-99-113112
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD123 Targeted Therapy with Talacotuzumab in Advanced MDS and AML after Failing Hypomethylating Agents - Final Results of the Samba Trial

Abstract: Introduction Recently, progress has been made in the treatment of patients with higher risk myelodysplastic syndromes (HR MDS) and acute myeloid leukemia (AML). Nevertheless, patients failing hypomethylating agents (HMA) have a dismal prognosis and very limited treatment options. Targeting CD123 on leukemic stem cells (LSC) is one promising approach in MDS and AML. Talacotuzumab (TAL, JNJ-56022473) is an IgG1 monoclonal antibody targeting CD123 preferentially via antibody-dependent cellular cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…24 AML patients, with a median age of 77 years were explored for response to talacotuzumab and five of these patients displayed a hematological improvement, corresponding to a partial response [127]. These observations suggest a limited benefit of this drug in this patient setting, a phenomenon related also to the compromised immune profile present in these patients (reduced mature NK cells, increased expression of inhibitory NK-cell receptors) [128].…”
Section: Therapeutic Cd123 Targetingmentioning
confidence: 99%
“…24 AML patients, with a median age of 77 years were explored for response to talacotuzumab and five of these patients displayed a hematological improvement, corresponding to a partial response [127]. These observations suggest a limited benefit of this drug in this patient setting, a phenomenon related also to the compromised immune profile present in these patients (reduced mature NK cells, increased expression of inhibitory NK-cell receptors) [128].…”
Section: Therapeutic Cd123 Targetingmentioning
confidence: 99%
“…Efficacy was limited in 24 patients (19 AML and 5 MDS) treated with the anti-CD123 antibody talacotuzumab, with an overall response rate of 20%, a median duration of response of 3 months, and a median OS of 3.2 months. 75 Other drugs. Despite the lack of a clear benefit in OS compared with best supportive care (median OS, 8.2 months vs 5.9 months) reported with IV rigosertib, a multikinase inhibitor, in a randomized phase 3 study in HR-MDS patients after HMA failure, the response rate for rigosertib-treated patients was higher than for patients receiving best supportive care (53% vs 17%), and post hoc analyses showed that patients with early HMA failure, as well as those with very high-risk IPSS-R or age , 75 years, could potentially have benefited from rigosertib.…”
Section: Targeted Molecular Therapies Idh1 (Ivosidenib) and Idh2mentioning
confidence: 99%
“…They reported that patients had significantly less mature NK cells and less activating NK-cell receptors compared to controls. Overall, their results showed moderate benefits of treating relapsed AML and MDS with monoclonal antibodies against CD123 only [ 81 , 82 ].…”
Section: Cd123-targeted Therapiesmentioning
confidence: 99%